2018
DOI: 10.1021/acscombsci.8b00113
|View full text |Cite
|
Sign up to set email alerts
|

Sea Urchin Embryo Model As a Reliable in Vivo Phenotypic Screen to Characterize Selective Antimitotic Molecules. Comparative evaluation of Combretapyrazoles, -isoxazoles, -1,2,3-triazoles, and -pyrroles as Tubulin-Binding Agents

Abstract: A series of both novel and reported combretastatin analogues, including diarylpyrazoles, -isoxazoles, -1,2,3-triazoles, and -pyrroles, were synthesized via improved protocols to evaluate their antimitotic antitubulin activity using in vivo sea urchin embryo assay and a panel of human cancer cells. A systematic comparative structure–activity relationship studies of these compounds were conducted. Pyrazoles 1i and 1p, isoxazole 3a, and triazole 7b were found to be the most potent antimitotics across all tested c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 79 publications
0
32
0
Order By: Relevance
“…In our previous work 3,4‐diaryl isoxazoles were identified as antimitotics with microtubule destabilizing mode of action . Therefore, the targeted 3,4‐diaryl‐isoxazole‐5‐carboxamides 6c–f , h , i were evaluated for antimitotic microtubule destabilizing activity using a phenotypic sea urchin embryo assay , . Antimitotic properties of a tested molecule were estimated by the ability to disrupt cleavage – quick successive embryonic cell divisions, whereas specific alteration of embryo motility, spinning on the bottom of the culture vessel instead of forward swimming, indicated microtubule destabilizing mechanism of action.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous work 3,4‐diaryl isoxazoles were identified as antimitotics with microtubule destabilizing mode of action . Therefore, the targeted 3,4‐diaryl‐isoxazole‐5‐carboxamides 6c–f , h , i were evaluated for antimitotic microtubule destabilizing activity using a phenotypic sea urchin embryo assay , . Antimitotic properties of a tested molecule were estimated by the ability to disrupt cleavage – quick successive embryonic cell divisions, whereas specific alteration of embryo motility, spinning on the bottom of the culture vessel instead of forward swimming, indicated microtubule destabilizing mechanism of action.…”
Section: Resultsmentioning
confidence: 99%
“…The sea urchin embryo assay was conducted as described previously , . Fertilized eggs and hatched blastulae were exposed to 2‐fold decreasing concentrations of compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…P. lividus embryo is a widely recognized model for several research programs spanning from cell proliferation assays [100] and differentiation patterns to toxicological studies [56,57,61,101,102,103,104,105,106,107,108], and also in poor-resource settings. Moreover, the sea urchin embryo has been also intensively used in order to select antimitotic compounds (and glean insights into the biological mechanism) from libraries of 1,3,4-oxadiazole derivatives [43], combretastatin derivatives [44,45] and analogues [109,110] and also 3-amino-thieno[2,3-b]pyridines [111].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] In our previous work, nitrostilbenes prepared from ANMs were utilized as starting materials for the synthesis of 3,4-diaryl-pyrroles and -isoxazoles. 6,7 The Victor Meyer reaction, [8][9][10][11][12][13][14][15][16][17][18][19] which involves the reaction of an alkyl halide with silver nitrite in a nonpolar solvent, e.g., diethyl ether or benzene, has been the method of choice for the preparation of ANMs since the 19th century. 1,11 In 1955, Kornblum reported that while p-nitrobenzyl bromide and benzyl bromide reacted with silver nitrite to form arylnitromethanes, the corresponding reaction of pmethoxybenzyl bromide gave predominantly a nitrite ester (55%) and small amount of p-methoxyphenylnitromethane (26%).…”
mentioning
confidence: 99%